Intrinsic Photoconductivity Spectral Dependence as a Tool for Prediction of Open-Circuit Voltage in Organic Solar Cells - Grzibovskis, Raitis; Polaks, Andis; Vembris, Aivars (MDPI, 2023)
Organic materials are known for their variety of molecules. Methods to predict the parameters of organic photovoltaic (OPV) cells are required to avoid the time- and resource-consuming processes of manufacturing and testing OPVs. Usually, the open-circuit voltage (Uoc) is estimated as the difference between the ionization energy level of the electron donor molecule (Id) and the electron affinity level of the electron acceptor molecule (EAa). Various measurement methods are used to determine the energy level values of pure materials, which, when combined with energy level shifts due to the donor:acceptor interactions, make these estimations less precise. In this work, photoconductivity measurements were applied to the donor:acceptor films. Near threshold energy, the electron can be directly transferred from the donor to the acceptor molecule. The obtained charge transfer energy (ECT) shows the difference between Id and EAa in the film. This difference was compared to the Uoc value of an OPV made of the same donor:acceptor combination. We show that this approach provides less scattered results and a higher correlation coefficient compared to the Uoc estimation using energy level values.--//-- This is an open-access article Grzibovskis, R.; Polaks, A.; Vembris, A. Intrinsic Photoconductivity Spectral Dependence as a Tool for Prediction of Open-Circuit Voltage in Organic Solar Cells. Energies 2023, 16, 6728. https://doi.org/10.3390/en16186728 published under the CC BY 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; organic photovoltaics; open-circuit voltage; intrinsic photoconductivity; bulk heterojunction